Promoting Human-Computer Interaction and Usability Guidelines and Principles Through Reflective Journal Assessment - Issa, Tomayess; Isaias, Pedro (IGI Global, 2014)
This chapter aims to examine the challenges to, and opportunities for, promoting Human Computer Interaction (HCI) and usability guidelines and principles through reflective journal assessment by information systems students from the Australian and Portuguese higher education sectors. In order to raise students’ awareness of HCI and aspects of usability, especially in the Web development process, a new unit was developed by the first researcher called Information Systems 650 (IS650) in Australia. From this unit was derived the Web Site Planning and Development (WSPD) course introduced in Portugal. The reflective journal assessment approach was employed to enhance students' learning and knowledge of HCI and its usability aspects. This study provides empirical evidence from 64 students from Australia and Portugal, based on quantitative and qualitative data derived from three sources: students’ formal and informal feedback and an online survey. Students confirmed that the use of reflective journal assessment consolidated their understanding of HCI and usability guidelines and principles and improved their reading, searching, researching, and writing skills, and their proficiency with the endnote software.